Effective Macroprudential Policy : Cross-Sector Substitution from Price and Quantity Measures - Cizel, Janko; Frost, Jon.; Houben, Aerdt; Wierts, Peter (Washington, D.C. : International Monetary Fund, 2016)
Macroprudential policy is increasingly being implemented worldwide. Its effectiveness in influencing bank credit and its substitution effects beyond banking have been a key subject of discussion. Our empirical analysis confirms the expected effects of macroprudential policies on bank credit, both for advanced economies and emerging market economies. Yet we also find evidence of substitution effects towards nonbank credit, especially in advanced economies, reducing the policies' effect on total credit. Quantity restrictions are particularly potent in constraining bank credit but also cause the strongest substitution effects. Policy implications indicate a need to extend macroprudential policy beyond banking, especially in advanced economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet